EFFECTS OF CREDIT INFORMATION SHARING ON NONPERFORMING LOANS: THE CASE OF KENYA COMMERCIAL BANK KENYA - Kwambai, Kipyego Daniel; Wandera, Moses (European Scientific Journal, ESJ, 2013)
Commercial banks play a pivotal role in the economy in the intermeadition process by mobilizing deposits from surplus units to deficit units. The surplus is channelled to deficit units through lending. Lending is the main activity of commercial banks in Kenya. However, banks in Kenya have had a high rate of loan default from the borrowers which have caused significant losses to the banks. This is because commercial banks have varied credit information and credit history about their borrowers and the credit seekers have taken this shortfall to get many loans from these banks which increases their rate of default because they might fail to service back all the loans. This study was therefore guided by objectives that sought to; find out the effects of credit information sharing on nonperforming loans in KCB Kenya and specifically to establish the trend of bad loans before and after the introduction of CRB, to identify the factors that account for bad loans and to determine the economic sector that records higher bad loans and the efforts taken to reduce the risk in this sector. Data was collected from primary sources and secondary data was collected from published financial statements of KCB between year 2007 to 2012. The researcher adopted a descriptive case research design and stratified proportionate random sampling technique was used to select the sample and data was analysed using both qualitative and quantitative methods and explanation given in prose.